Analysis of Balanced Scorecard Implementation as Performance Management System at Deputy for Law Enforcement – Indonesian FDA - Linda Octaviani; Yudo Anggoro (Journal of International Conference Proceedings (JICP), 2021)
Deputy for Law Enforcement (Deputy IV) is a strategy for strengthening the Indonesian FDA (BPOM) in responding to future law enforcement challenges that have functions and duties of the regulation and comprehensively eliminate crime in the Drug and Food sectors. They required a well-planned strategic plan to carry out their tasks and responsibilities, including a performance management system based on the Balanced Scorecard (BSC) approach. This research aims to evaluate the effectiveness of Balanced Scorecard (BSC) implementation at Deputy IV. The qualitative descriptive methodology was used in this research, analyzing primary data sources obtained through interviews with internal stakeholders. The result shows that there are essential factors on each system performance evaluation category such as integrity, commitment, responsibility, strategy map, key performance indicator (KPI), cascading, valid and balanced measurement, realistic target, individual and objective alignment, cascading, human resources, budgeting process, strategic planning process, data collection, and reporting. The recommendation, Deputy IV must be maintained the essential factors of BSC implementation to improve their future performance. This research is intended to assist public officials as policymakers in strategic planning and performance management evaluation.